GENDER DIFFERENCES IN HIGH SCHOOL STUDENTS' CAREER ADAPTABILITY - Sahin, Arif; Sugiharto, Dwi Yuwono Puji; Sunawan, Sunawan; Mulawarman, Mulawarman (Counsenesia Indonesian Journal Of Guidance and Counseling, 2025)
The Industrial Era 5.0 has brought significant changes to the fields of education and employment, including the financial and educational sectors, through the utilization of AI and blockchain technologies. This study aims to explore the influence of career adaptability among high school students in terms of gender differences. The research involved 452 students from public senior high schools across Semarang City. Data analysis was conducted using hypothesis testing through the Mann Whitney U Test, preceded by tests of normality and homogeneity using the JASP software. The results indicated that male students demonstrated a higher level of career adaptability compared to female students. This study also highlights the importance of social support and education that is responsive to adolescents' needs, as well as the necessity for inclusive and relevant career education policies in alignment with the demands of Era 5.0. Recommendations for future research include exploring broader social and cultural contexts and examining the impact of technology on career adaptability